2022
DOI: 10.1097/rlu.0000000000004368
|View full text |Cite
|
Sign up to set email alerts
|

Primary Neuroendocrine Carcinoma of Pineal Gland With Extensive Meningeal Metastasis Detected by 18F-NOTATATE PET/CT

Abstract: Primary neuroendocrine tumor of the pineal gland is a rare disease. A 44-year-old woman with right cerebellopontine angle metastatic small cell neuroendocrine carcinoma underwent 18 F-FDG and 18 F-NOTATATE PET/ CT scans. 18 F-NOTATATE PET/CT showed intense uptake in the pineal gland lesions and multiple foci of intense focus of uptake in the intracranial leptomeningeal and whole spinal canal. However, the lesions are less impressive on 18 F-FDG PET/CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Surgical management of metastatic disease is a mainstay for this pathology, followed by adjuvant chemoradiotherapy [ 104 ]. Another case study identified a primary neuroendocrine tumor of the pineal gland with drop metastasis to the spine [ 105 ]. Choroid plexus carcinoma is a rare intraventricular neoplasm affecting children.…”
Section: Primary Central Nervous System Tumorsmentioning
confidence: 99%
“…Surgical management of metastatic disease is a mainstay for this pathology, followed by adjuvant chemoradiotherapy [ 104 ]. Another case study identified a primary neuroendocrine tumor of the pineal gland with drop metastasis to the spine [ 105 ]. Choroid plexus carcinoma is a rare intraventricular neoplasm affecting children.…”
Section: Primary Central Nervous System Tumorsmentioning
confidence: 99%
“…The tumors exhibit a male predilection, with a ratio of nearly 3:1, and almost 90% of cases arise in the head and neck, particularly in the upper aerodigestive tract 1–8 . Various other sites for the presentence of solitary extramedullary plasmacytomas have been documented, 9 including gastrointestinal tract, 10,11 breast, 6 lung, 12 liver, 13 anterior mediastinum, 14 and retroperitoneum 15 . It should be noted that solitary extramedullary plasmacytoma involving the penis, particularly the corpora cavernosa, is extremely rare 16 .…”
mentioning
confidence: 99%
“…Tragically, the patient’s clinical state rapidly deteriorated due to multiorgan failure, leading to death 26 days following admission. Plasma cell myeloma patients may display atypical myelomatous presentation 1–7 . Previous challenging cases with hematologic and solid malignancies were reported with hepatic superscan, 8–11 but no cases of coexisting hepatosplenic superscan in hematologic malignancies have been documented.…”
mentioning
confidence: 99%